Determinants of MSME Tax Compliance: Tax Knowledge, Tax Rates, and Digitalization - Fitri Ritonga; Rahmat Daim Harahap; Budi Harianto (Universitas Muhammadiyah Makassar, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) remains a persistent challenge in Indonesia, particularly in urban centers such as Medan City where registered taxpayer numbers far exceed actual filing rates. This study aims to analyze the influence of tax knowledge, tax rates, and the use of digital technology‑based tax administration systems on MSME tax compliance. A quantitative explanatory design was employed, utilizing primary data collected through structured questionnaires distributed to 100 MSME taxpayers registered at KPP Pratama Medan Polonia, selected via purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 23, preceded by validity, reliability, and classical assumption tests. The results reveal that partially, tax knowledge (t = 5.911, p < 0.05), tax rates (t = 2.499, p < 0.05), and the digital tax administration system (t = 2.812, p < 0.05) each exert a positive and significant effect on tax compliance. Simultaneously, the three variables significantly influence compliance (F = 51.674, p < 0.05), explaining 61.8% of its variance (R² = 0.618). Among the predictors, tax knowledge demonstrates the strongest relative influence. These findings underscore the importance of enhancing tax education, maintaining equitable rate policies, and optimizing user‑centric digital tax platforms to foster sustainable compliance within the MSME sector. The study contributes to the theoretical discourse by integrating the Theory of Planned Behavior and the Technology Acceptance Model within the tax compliance domain.